Decadal changes and Spatial Variations in Female Literacy in Faizabad District, Uttar Pradesh - Sharma, Vivek Kumar; Rai, Vinay Kumar (National Geographical Journal of India, 2022)
The economic performance and social development of a country depend to a considerable extent upon the educational status of its citizens . Education is also considered as an indicator of socioeconomic development. It is estimated that a high percentage of all illiterates of the world are found in developing countries in which female are in majority. Female in these countries face disparity in social, cultural, economic and schooling opportunities. The main reasons are prevailing patriarchal ideology, poor school environment for girls, low enrollment of girls, dowry system, early marriage, poverty, localism and education level of parents etc. The total literacy of Faizabad district in the year 2011 was 68.73%, while male literacy rate in the district was 78.12%,literacy rate was only 59.03%. Efforts are being made by the government and non-government organizations to promote the education of female. The result of these efforts is that females are becoming more ambitious and has started participating in all modern professions (medicine, engineering, teaching, law and management, etc.).